Physiological responses and time-motion characteristics of young tennis players: comparison of serve vs. return games and winners vs. losers matches - Kilit, B.; Arslan, E. (International Journal of Performance Analysis in Sport, 2017)
The aim of this study was to compare the physiological responses and time-motion characteristics of young tennis players between serve vs. return games and winners vs. losers matches during simulated tennis match play. Heart rate (HR) and skin temperature (ST) were monitored along with total distance covered in four different speed zones—walking, low-intensity running, moderate-intensity running and high-intensity running, using two portable multivariable integrated 10 Hz GPS monitoring devices over fourteen outdoor clay court matches; ratings of perceived exertion were also determined at the end of the game. Variables describing the characteristics of the matches determined from video recordings were: strokes per rally, rally duration, effective playing time, work-to-rest ratio and rest time between rallies. The results showed no significant differences in physiological responses and time-motion characteristics both serve vs. return games and winners vs. losers matches (p > .05). These findings might be used for the training programmes in order to improve the tennis-specific technical and performance required for young tennis players.